Two-level frame aggregation with enhanced A-MPDU for signal-to-noise ratio efficiency in IEEE 802.11n WLANs - Fatoumata Sorra; Mohamed Othman; Umar Ali Bukar; Fahrul Hakim; Mohamed A. Alrashah; Anvar Saif; Mehrnaz Moudi (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
One of the most important frame aggregation features for enhancing the speed of IEEE 802.11n wireless local area networks (WLANs) through sharing headers and timing overheads is an aggregate MAC protocol data unit (A-MPDU). However, because aggregation overhead affects A-MPDU frame size, the A-MPDU performance falls short of user expectations. The variable signal-to-noise ratio (SNR) is significantly decreased as a result of the influence of lost sub-frame on the volume of sub-frames that may be aggregated (the level of aggregation). In order to solve this issue, this study suggests an improved A-MPDU with reduced header overheads as well as a efficient two-level aggregation technique based on enhanced A-MPDU. To test the suggested plan, a simulation experiment was run on NS-3. The results show that the suggested two-level aggregation approach works better than the existing methods by achieving higher throughput, SNR, and a efficient medium access control (MAC) layer.